Student inspired pedagogy: Students' beliefs and preferences regarding second language academic writingegarding second language - Ilina Kachinske (University American College Skopje, 2022)
By adopting a student-inspired pedagogy, this preliminary study attempts to answer questions about second language (L2) writing pedagogical practices in higher education by examining student attitudes, beliefs and preferences on L2 academic writing. In particular, the pilot study analyzes student beliefs concerning the most effective timing and type of feedback provided by the instructor. The study reports on the preliminary results from a questionnaire given to 36 first-year students at a university in North Macedonia. The results of the pilot study are discussed in the light of the theoretical and pedagogical implications that can be applied in L2 writing, teacher development and curriculum design settings.
Keywords: 330; second language writing; second language pedagogy; student beliefs; corrective feedback